1988
DOI: 10.1063/1.100611
|View full text |Cite
|
Sign up to set email alerts
|

Crystallography and microstructure of Tl-Ca-Ba-Cu-O superconducting oxides

Abstract: We report on the crystallography and microstructure of six oxides in the Tl-Ca-Ba-Cu-O system with nominal compositions Tl1Ba2Cu1O5, Tl1Ca1Ba2Cu2O7, Tl1Ca2Ba2Cu3O9, Tl2Ba2Cu1O6, Tl2Ca1Ba2Cu2O8, and Tl2Ca2Ba2Cu3O10. The structures consist of one, two, or three Cu perovskite-like units sandwiched between Tl-O monolayers or bilayers. The predominant defects in the crystals with bilayer and trilayer Cu perovskite-like units are stacking faults that produce local intergrowths of related structures. The density of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Similar distortions are found in Tl-2212 by the pair-distribution-function (PDF) analysis of neutron scattering data [16,17]. It appears that these distortions not only have short-range correlations, but may in some cases also have long-range correlations, as evidenced by the presence of the modulational structure for selected sections, observed in high-resolution electron microscopy and electron diffraction [18][19][20][21][22]. In addition, the temperature dependence of the local structure in the CuO 2 plane has been studied by XAFS in Tl-2201 [23,24] and by PDF in Tl-2212 [25], respectively.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Similar distortions are found in Tl-2212 by the pair-distribution-function (PDF) analysis of neutron scattering data [16,17]. It appears that these distortions not only have short-range correlations, but may in some cases also have long-range correlations, as evidenced by the presence of the modulational structure for selected sections, observed in high-resolution electron microscopy and electron diffraction [18][19][20][21][22]. In addition, the temperature dependence of the local structure in the CuO 2 plane has been studied by XAFS in Tl-2201 [23,24] and by PDF in Tl-2212 [25], respectively.…”
Section: Introductionmentioning
confidence: 59%
“…Long range order modulations have been observed in Bi-Sr-Ca-Cu-O superconductors and related materials [43]. Some long range order in the TlO layers is also observed in Tl-2201 and Tl-2212 by electron diffraction and highresolution transmission electron microscopy [18][19][20][21][22]. The modulation wave vector is about < −0.16, 0.08, 1 > for tetragonal Tl-2201 (a = b ≃ 3.8 Å), < 0.08, 0.24, 1 > for orthorhombic Tl-2201 (a ≃ b ≃5.4 Å), and < 0.17, 0, 1 > for tetragonal Tl-2212.…”
Section: The Question Of Long Range Ordermentioning
confidence: 99%
“…4 and the atomic displacement parameters in Table 4 that the refinement fails to fully capture the structure in the Ba-O and Tl-O layers. This can be dealt with by splitting the Tl and O(3) sites [23,16,17,13], which provides limited information about which directions each site departs from its symmetric position, while some studies have identified satellite peaks corresponding to an incommensurate superlattice modulation in the TlO layers [25,20,22]. Simulated precession photographs were generated from the diffraction data, to help clarify the crystal structure.…”
Section: Sourcementioning
confidence: 99%
“…This structural aspect is prosaically, yet strikingly, manifested when one grinds Bi-2223 and Y-123 in a mortar and pestle... the former yields a "greasy" graphitic feel and the latter a very granular one like trying to grind sand. Some of the other Bi-2223-like structures that are candidates for wire embodiments are Tl-1223 [20], Bi-2212 [21] and Hg-1223 [22] which have successfully been fabricated on Ag tape substrates. In particular, Bi-2212 shows great promise as wire for low-temperature magnet application at liquid He because of its very high H C2 .…”
Section: A Htsc Wire Materialsmentioning
confidence: 99%